The Effect of Using Instagram Short Video Media Towards Students’ Vocabulary Mastery at The Seventh Grade of Babunnajah Junior High School Menes-Pandeglang - Enasaroh, Enasaroh; Sudirman, Ade; Novari, Ari Fajria (Universitas Mathla'ul Anwar Banten, 2022)
The research aims to investigate the effect of using Instagram short video media towards student’s vocabulary mastery at the seventh grade of Babunnajah junior high school Menes-Pandeglang in the academic year 2021-2022. This research used quantitative approach and quasi-experimental method with achievement test in collecting data. Achievement test include pre-test and post-test. Short Instagram videos are used as learning media to help students master vocabulary. Jagobahasacom is the Instagram account used as the video source. The experimental class for this research was seventh grade B, and the control class was seventh grade A. Each class has 20 students, for a total of 40 samples in all. The experimental class's mean score on the pretest was 62.15, while the control class's score was 59.45. Following the acquisition of posttest results, the experimental class had a mean score of 70.65, whereas the control class received a score of 66.3. Hypothesis testing is done by comparing T-table with T-count. The results obtained from hypothesis testing are -1.686 > -3.068, this result indicated that H0 was rejected and Ha was accepted. As a result, hypotheses test indicated that there is significant effect of using Instagram short video media towards student’s vocabulary mastery at the seventh grade of Babunnajah junior high school Menes-Pandeglang.